Endothelin-B Receptors and Left Ventricular Dysfunction after Regional versus Global Ischaemia-Reperfusion in Rat Hearts - Sofia-Iris Bibli; Eleni V. Toli; Agapi D. Vilaeti; Varnavas C. Varnavas; Giannis G. Baltogiannis; Apostolos Papalois; Zenon S. Kyriakides; Theofilos M. Kolettis (Cardiology Research and Practice)
Background. Endothelin-1 (ET-1) is implicated in left ventricular dysfunction after ischaemia-reperfusion. ETA and ETB receptors mediate diverse actions, but it is unknown whether these actions depend on ischaemia type and duration. We investigated the role of ETB receptors after four ischaemia-reperfusion protocols in isolated rat hearts. Methods. Left ventricular haemodynamic variables were measured in the Langendorff-perfused model after 40- and 20-minute regional or global ischaemia, followed by 30-minute reperfusion. Wild-type (n=39) and ETB-deficient (n=41) rats were compared. Infarct size was measured using fluorescent microspheres after regional ischaemia-reperfusion. Results. Left ventricular dysfunction was more prominent in ETB-deficient rats, particularly after regional ischaemia. Infarct size was smaller (P=0.006) in wild-type (31.5±4.4%) than ETB-deficient (45.0±7.3%) rats after 40 minutes of regional ischaemia-reperfusion. Although the recovery of left ventricular function was poorer after 40-minute ischaemia-reperfusion, end-diastolic pressure in ETB-deficient rats was higher after 20 than after 40 minutes of regional ischaemia-reperfusion. Conclusion. ETB receptors exert cytoprotective effects in the rat heart, mainly after regional ischaemia-reperfusion. Longer periods of ischaemia suppress the recovery of left ventricular function after reperfusion, but the role of ETB receptors may be more important during the early phases.